Etude de quelques propriétés probiotiques des quelques souches Lactobacillus isolées de lait chamelle et de chèvre - RAKHIS, SAMIA; LADJAL, HABIBA (My University, 2016)
Our study aims to evaluate certain probiotic strains Lactobacillus skills 8 isolated from camel milk and goat, ie S1, S2, S3, S4, S5, S6, S7 and S8. Indeed the resistance to acid PH of the stomach and bile salts was tested in these strains. Exposure of Lactobacillus strains to acidic pH of 2, 3 and 6.8 for 180 minutes. At PH 2, that is the S8 strain which showed a maximum viability rate which is of the order of 57% compared to other strains, followed by the strains S4, S3 and S5 with the viability rate of the order of 38,30 and 29% respectively. Resistance to contact with a solution containing 0.5g / l bile salts, showed that strains S4, S5, S1, S6, S3 and S7 resisted to bile salts with respective viabilities rate of 90, 82.5, 80, 75, 69, 23 and 66.12%, on the other hand, strains S2 and S8 weakly resisted these conditions with viability rates of 55.55 and 44.94% respectively.
Keywords: Lactobacillus; probiotic; bile salts; gastric PH; Lactobacillus; probiotique; sels biliaires; PH gastrique